Bleeding with anticoagulation therapy – Who is at risk, and how best to identify such patients - Palareti, Gualtiero; Cosmi, Benilde (Thrombosis and Haemostasis, 2009)
Anticoagulation with vitamin K antagonists (VKAs) has been shown to be effective in the prevention and treatment of thrombotic complications in various clinical settings, including atrial fibrillation (AF), venous thromboembolism (VTE), acute coronary syndromes and after invasive cardiac procedures. Bleeding is the most important complication of VKAs and a major concern for both physicians and patients. The occurrence of bleeding during treatment is not only important for the treated subjects, but also for a correct and complete use of this therapy in all the subjects who have a clear clinical indication for anticoagulation. This review analyses the treatment- and person- associated risk factors for bleeding during VKAs and their combination in clinical prediction rules that have been proposed in the attempt to identify those patients at higher risk for bleeding. The clinical prediction rules may help physicians stratify patients into categories of risk and thus to evaluate their individual risk/benefit ratio of starting or prolonging an anticoagulant treatment.
Keywords: Anticoagulation; bleeding; vitamin K antagonists; clinical prediction rules